Effectiveness of mushrooms Trichoderma herzianum in the biological resistance of two types of mushrooms Fusarium isolated from the seeds of cloves - Nadeem Ramadan (College of Education for Pure Sciences, 2007)
ABSTRACT The present study was able to isolate eight different species and yeast of seed born fungi from carnation seed (Dianthus caryophyllus ), six of which belong to the class Deuteromycetes, one to the class Ascomycetes, and one to the class Zygomycetes . The percentages of isolation were 7% Alternaria alternata , 1% Fusariun colmorum, and 1% F. oxysporum . The infection with these fungi caused reduction in the seed germination ratio to 28% and 16 % in the seed of the local cultivar and the red (Dwarf) with F.oxysporum respectively . while seeds of white cultivor (Doppio) exhibited ratios of 60% and 80% with both species of Fusarium. The biological controller Trichoderma herzianum had a clear effect on the growth of both species of the Fusarium and the antagonism degree 1.3 and 1.6 respectively. Fusarium oxysporum producd more polygalacturonase , pectatelyase and showed a clear zone 6 cm diameter around the fungal colony.